Viscosupplementation for improvement in pain and mobility in knee osteoarthritis : A retrospective cross sectional study. - Muhammad Ahsan Sulaiman; Javeria Saeed; Koonj Sundardas; Masood Umer (Journal of the Pakistan Medical Association, 2026)
Objective: To evaluate pain and mobility improvement in knee osteoarthritis patients after hyaluronic acid viscosupplementation. Method: The cross-sectional, retrospective study was conducted at the Department of Orthopaedics, Aga Khan University Hospital, Karachi, and comprised data from January 2019 to December 2022 of patients having knee osteoarthritis who had received viscosupplementation with hyaluronic acid gel. Western Ontario and McMaster Universities Osteoarthritis Index score was calculated at baseline and on patient follow-up at 12 months. Data was analysed using SPSS 23 Results: Of the 180 patients with mean age 61.1+/-11.4 years, 109(60.6%) were females and 71(39.4%) were males. Mean baseline score was 69.6+/-8.3, which went down to 48.2+/-10.6 post-intervention (p<0.05), with significantly greater improvement in patients with mild to moderate knee osteoarthritis compared to those with advanced osteoarthritis (p<0.05). Conclusion: Viscosupplementation with hyaluronic acid significantly improved outcomes in knee osteoarthritis cases over one year. Benefits were more notable in mild to moderate cases. Key Words: Knee osteoarthritis, Hyaluronic acid gel, WOMAC score, Viscosupplementation, Improvement in pain. Level of Evidence : IV